Investigating the Implementation of an Online Literacy Coaching Program for Junior High School English Teacher (NOBEL: Journal of Literature and Language Teaching, 2022)
Literacy coaching is an in-depth style of literacy enrichment and professional development activity that links observation, feedback, and reflection to the practice. This study adopted a case study to investigate the implementation, process, and benefits of an online literacy coaching program for 32 junior high school English teachers across Indonesia. Observation protocol recorded sessions, and participants were the data sources of this study. As observed thus analyzed through content analysis, it was found that the implementation of online literacy coaching has fulfilled the core activities of literacy coaching cycles as it adopts a collaborative, reflective, and project-based approach. In further, the process of literacy coaching has improved the participants' literacy teaching as their performance in Cycle 2 was getting better than in Cycle 1. Moreover, the interview and questionnaire results showed that the implementation of Online Literacy Coaching improved the participants' literacy skills and pedagogy. Based on the findings, this study proposed recommendations to properly emphasize the time duration of each session, intensively establish digital literacy even further, and intentionally involve students’ feedback as valuable and beneficial input for teachers’ professional development and the process of online literacy coaching.